The responsibility to rebuild and Jus Post Bellum : mapping the normative discourse on stabilization in Libya from 2011 to 2020 - Schoeman, Maxi (University of Pretoria, 2024)
Thesis (PhD (International Relations))--University of Pretoria, 2023.